Axillary Reverse Mapping in the Prevention of Lymphoedema: A Systematic Review and Pooled Analysis - Co, Michael; Lam, Lucia; Suen, Dacita; Kwong, Ava (Clinical breast cancer, 2023)
This is a systematic review of randomized controlled trials (RCT) comparing the use of axillary reverse mapping (ARM) with conventional technique for axillary dissection (AD) in breast cancer surgery. This review was written in line with the PRISMA protocol. Articles were retrieved from PubMed, EMBASE, CINAHL and Cochrane databases, using keywords ..úaxillary reverse mapping..Ñ and “axillary lymph node dissection”. Non-RCT were excluded. Abstracts were screened independently by 2 reviewers. Data from eligible studies were retrieved for qualitative synthesis and pooled analysis. 73 publications were identified for initial screening. 68 articles were excluded from analysis according to the pre-defined systematic review protocol. 5 RCTS with 1696 subjects were included for analysis. 802 patients received ARM, 894 patients received AD. Pooled ARM node detection rate was 84.9% (Range 79.2 - 94.9%). There was a lower rate of post-operative lymphedema in ARM group patients across all 5 RCTs. The pooled lymphedema incidence in the ARM group was 4.8% (37/766) when compared to 18.8% (164/873) in the AD group (P < .0001). Axillary recurrence rate with median followof 37 months was 1.03% (8/778) in the ARM group, which was identical to 1.03% (9/870) in the AD group (P = 1). ARM resulted in decreased incidence of lymphedema. There was no significant increase in axillary recurrence at 37 months post-operation.